2014
DOI: 10.1167/iovs.14-13880
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Correction of Ocular Magnification on Spectral-Domain OCT Retinal Nerve Fiber Layer Measurement Variability and Performance

Abstract: Correction of RNFL measurements for ocular magnification did not improve prediction limits in normal subjects or enhance the performance of SD-OCT in this group of eyes in which the axial length did not deviate significantly from average values. The cross-sectional area of the RNFL was not related to the optic disc area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
4
26
1
Order By: Relevance
“…However, Nowroozizadeh et al used customized measurement circles in normal and glaucomatous eyes and found that a correction with ocular magnification did not improve global or regional structure-function relationships [18]. Compared to Nowroozizadeh et al's study, the myopic subjects in the current study had longer axial length.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…However, Nowroozizadeh et al used customized measurement circles in normal and glaucomatous eyes and found that a correction with ocular magnification did not improve global or regional structure-function relationships [18]. Compared to Nowroozizadeh et al's study, the myopic subjects in the current study had longer axial length.…”
Section: Discussioncontrasting
confidence: 52%
“…Compared to Nowroozizadeh et al's study, the myopic subjects in the current study had longer axial length. According to Bennett's formula, axial length affects the magnification of the ocular optic system by a scaling factor expressed as (24.46 − 1.82)/( AL ⁡−1.82) [17, 18]. Axial length is also linearly correlated with refraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, images obtained from highly myopic eyes were corrected for magnification using Bennett's formula. 16,17 The relationship between OCT image measurements and actual scan diameter was expressed by the formula t ¼ p 3 q 3 s, where t represents the actual scan length, p represents the magnification factor determined by the OCT imaging system camera, q represents the magnification factor in relation to the eye, and s represents the original measurement value obtained from the OCT image. The correction factor q is expressed by the equation q ¼ 0.01306 3 (AL -1.82) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The actual size of the scan circle in the eye increases at higher ALs (because of ocular and photographic magnification). In fact, the real scan circle size in an eye with an AL greater than 24.46 mm or a refractive error less than zero diopter would be larger than the normal size and vice versa . Therefore, because RNFL thickness decreases at more distant points from the optic disc, underestimation of the average RNFL thickness is expected .…”
Section: Discussionmentioning
confidence: 99%